Deleuze and Guattari : aesthetics and politics - Porter, Robert, 1972- (Political philosophy now., 2009)
This book examines the relationship between aesthetics and politics based on the philosophies of Gilles Deleuze (1925-1995) and Pierre-Felix Guattari (1930-1992), most famous for their collabarative works Anti-Oedipus (1972) and A Thousand Plateaus (1980).